Badanie podobieństwa strategii inwestycyjnych funduszy małych i średnich spółek w Polsce - Salamaga, Marcin (Research of the Similarities of Investment Strategies of the Mutual Funds Investing in Small- and Medium-Sized Companies in Poland, 2009)
The paper presents the structure of the mutual funds portfolios in terms of the type of assets, companies, branches and sectors of the economy. The author proposed the application of Ward's clustering method and the ratios of structures similarity to classify the mutual funds with a similar pattern of investment portfolios. The author used the market, economic and financial ratios to research the mutual funds investing in small- and medium-sized companies in Poland between 2006 and 2008. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 157-164